Penampilan Galur Harapan Padi Sawah di Kabupaten Solok Sumatera Barat - Zen, Syahrul (Jurnal Penelitian Pertanian Terapan, 2013)
Superior varieties is one component of the innovative technology that is reliable and gives a real contribution to the success of an increase in the productivity of food crops in Indonesia. To that end, the discovery of new superior variety is continuously carried out absolute in order to anticipate changes in the structure of the plant organism, the situation is very dynamic, the resilience of a superior varieties of plant organism could not last long. Testing adaptation promissing lines is one of the stages approach to filter lines that are capable of adapting well and has high yield potential. In 2009 has been carried out 10 test promissing lines of rice fields on two locations in Solok Regency of West Sumatra from Agustus 2009 to Januari 2010. The experiment used a randomized complete block design, with four replication was used, plot size 4.0 m x 5.0 m Fertilizer aplicated at rate of 280 kg of Urea, 100 kg SP 36 and 100 kg KCl/ha. The results showed promissing lines BP10620F-BB4-15-BB8 and BP2842E-14-2 were 21.50% and 21,72% more than varieties IR42. Plant high posture all the promissing lines including the ideal that is with the range of 85-105 cm. Keywords: Rice, Promissing liness,